Tantangan Belajar Online pada SD Negeri 064037 - Hasian Rambe; Mia Audina Naibaho; Siti Masdelina Siregar; Lukmawati Lukmawati; Lailatul Adila purba; Mely Suryani (Edumaspul: Jurnal Pendidikan, 2022)
This research aims to ascertain how the challenges of online learning are during the covid 19 pandemic. The researcher uses a qualitative approach with a descriptive method. The researcher uses a questionnaire to collect data. The research subject in this paper is the principle of SDN 064037. The results show that the online learning system is no more effective than the face-to-face learning system due to the virtual learning system or from causing many obstacles.